2019
DOI: 10.1186/s12935-018-0714-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD59 inhibits apoptosis of T-acute lymphoblastic leukemia via AKT/Notch1 signaling pathway

Abstract: BackgroundT-acute lymphoblastic leukemia (T-ALL) was a hematological malignancy characterized by the accumulation of immature T cells in bone marrow and peripheral blood. In this study, we tried to explore the physiological role of CD59 in T-ALL.MethodsIn this study, we collected the bone marrow samples from 17 T-ALL patients and 38 healthy participants to find differences in CD59 expression patterns. Then, CD59 was over-expressed in T-ALL cell line Jurkat, and its biological functions were detected. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The expression of CD59 was increased in HCC on both of mRNA and protein levels. This was also reported in different cancer tissues because of its great role in enhancing tumour growth . The level of serum CD59 was also increased in HCC when compared with control.…”
Section: Discussionsupporting
confidence: 64%
“…The expression of CD59 was increased in HCC on both of mRNA and protein levels. This was also reported in different cancer tissues because of its great role in enhancing tumour growth . The level of serum CD59 was also increased in HCC when compared with control.…”
Section: Discussionsupporting
confidence: 64%
“…MAC has been found to activate pathways in cancer cells that inhibit death signals and induce mechanisms of evasion of complementdependent cytotoxicity, such as blocking MAC assembly and increasing MAC elimination from the cell surface. 65 Increased presentation of CD59 on leukemic cancer cells reduces effectiveness of rituximab by inhibiting apoptosis 66,67 and on tumor cells leads to increased tumor progression in a model of neuroblastoma. 68 Cancer cells activate protective pathways, including CD46, CD55, and CD59, to inhibit complement activation to reduce number of MAC inserted to counteract death signals.…”
Section: Mac In Cancermentioning
confidence: 99%
“…Indeed, we discovered a significant reduction in CD59 and FLAER expression in AML, impairing AML pathophysiology. Recent studies revealed that proportion of T lymphocytes expressing CD59 was significantly higher in the bone marrow of T-ALL patients than in healthy individuals, 29 but the molecular mechanism by which this predicts poor prognosis and disease progression remains unclear.…”
Section: Discussionmentioning
confidence: 99%